Variational EM for binaural sound-source separation and localization - Deleforge, Antoine; Forbes, Florence; Horaud, Radu (IEEE International Conference on Acoustics, Speech and Signal Processing, 2013)
The sound-source separation and localization (SSL) problems are addressed within a unified formulation. Firstly, a mapping between white-noise source locations and binaural cues is estimated. Secondly, SSL is solved via Bayesian inversion of this mapping in the presence of multiple sparse-spectrum emitters (such as speech), noise and reverberations. We propose a variational EM algorithm which is described in detail together with initialization and convergence issues. Extensive real-data experiments show that the method outperforms the state-of-the-art both in separation and localization (azimuth and elevation
LMS::1516